The impact of the supply chain management policy on the Limpopo office of the premier - Chauke, Dzunekani David (My University, 2021)
The South African government introduced the Supply Chain Management Framework in 2003, with a vision of creating a seamless system intended to play a critical role in service delivery to communities while achieving the objectives of cost-effectiveness, fairness, equity, transparency and ethics. This study focused on the impact of Supply Chain Management Policy Implementation in the Limpopo Office of the Premier. Qualitative data were collected, primarily in the form of semi-structured interviews using an interview schedule consisting of both closed and open-ended questions with the Chief Financial Officer, Director (SCM), Deputy Directors (Demand, Acquisition, Logistics and Inventory, Asset and Transport Management) and SCM nineteen SCM practitioners. These officials provided sufficient information concerning the effect of Supply Chain Management policy implementation in the Limpopo Office of the Premier. The study established that failure to implement SCM policy hurts service delivery. The effective implementation results in improved service delivery, whereas poor implementation results in the poor quality of service to the public, fraud and corruption, irregular and fruitless expenditures as well as negative departmental image.
Thesis (MPAM.) -- University of Limpopo, 2021
Keywords: Supply chain; Management policy; Supply Chain Management; Marketing channels -- Management; Supply chain management; Business logistics -- Management; Marketing -- Management